پاکستان میں فقہ و افتا کے خدوخال: جائزہ اور تجاویز - محمد زاہد (FIKR-O NAZAR فکر ونظر, 2013)
The institution of fatwa, in the Indian subcontinent, bears distinctive features owing to its geographical location, history and diverse challenges that it has confronted with. The present article tries to focus on the development of this institution in Pakistan and studies its existing important futures with a critical lens. It maintains, that since there exist different spheres of legislation viz. individual level, community level and the state level in the modern modes opting the traditional fatwa strategy to deal with the issues of all spheres does not helps to counter the challenges in a better way.